Systematic Review of Valve Surgery with Continuous Coronary Perfusion on Beating Heart in Patients with Low Left Ventricular Ejection Fraction. - Khayrullaev , Umid; Mullabaeva, Guzal; Sharipov, Islamjan (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. Beating-heart continuous coronary perfusion (BHCCP) is an alternative to cardioplegic arrest in valve surgery, potentially reducing ischemic reperfusion injury, especially in high-risk patients with low left ventricular ejection fraction (LVEF).Materials and methods. A systematic review of prospective and observational studies was conducted, focusing on BHCCP versus cardioplegia in valve surgery, with emphasis on patients with LVEF